Socialpreneurship 5.0: A Digital Workflow Innovation Model for Enhancing MSME Competitiveness and the Creative Economy through Community Partnerships in Kepulauan Seribu - Wahono, Puji; Hamdani, Fajri; Aditya, Shandy; Fadlullah, Fauzan (Abdimas Indonesian Journal, 2025)
Tidung Island in the Kepulauan Seribu district is home to many micro, small, and medium enterprises (MSMEs) that remain dependent on manual bookkeeping and traditional marketing practices. These limitations reduce operational efficiency and restrict their market reach. To address this, the Socialpreneurship 5.0 program was introduced, featuring SmartFlow dashboards designed on the Notion platform. The system combines three functions: digital financial records, structured social media content planning, and automated business content generation. The program progressed through five stages; socialization, training, application, mentoring, and sustainability, implemented through collaboration between universities, local government, and MSME partners. Outcomes indicate that more than 80% of daily transactions were digitally recorded, monthly financial reports became routine, and social media engagement rose by over 30%. Students also produced five digital business models, and a local MSME digital community was formed. By linking directly to SDGs 8, 9, and 17, the initiative demonstrates how digital inclusion and multi-stakeholder collaboration can strengthen creative economy actors in coastal communities.